Analisis pengelolaan keuangan islam pada usaha bisnis online Yulianinghoky Multibeauty Skincare di Kabupaten Tulungagung - Sapnawati, Rizka Alifia; Hidayati, Amalia Nuril (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The rise of online business entrepreneurs at this time, in the midst of the COVID-19 pandemic situation with restrictions on social activities, makes online-based businesses an alternative that can be considered. This research is focused on the Islamic financial management side of online business. No exception in managing finances in a business. With Yulianinghoky's multibeauty skincare business as an object of research with Islamic financial management applied in online business. The focus of the research in this journal is (1) How is financial management in the online business of Yulianinghoky multibeauty skincare? (2) Is the financial management of the Yulianinghoky multibeauty skincare business in accordance with the principles of Islamic financial management? (3) What are the obstacles in managing Yulianinghoky's multibeauty skincare online business? (4) What is the solution to the problems in managing Yulianinghoky's multibeauty skincare online business?. This research method uses a qualitative research approach with the type of case study research.. The results of this study indicate that these micro business actors or online business actors have not implemented Islamic management because they still contain unclear elements in the distribution of profits and the cost of their products (gharar).